Perlindungan Hukum Korban Money Game Dengan Skema Piramida Dan Skema Ponzi Di Indonesia - Wibowo, Ari Tri (Universitas Muhammadiyah Kotabumi, 2025)
Pyramid schemes and Ponzi schemes are different although there are similarities between the two, the current regulations in Indonesia only regulate the prohibition of illegal investment in general, and also regulate the prohibition of pyramid schemes, while regulations regarding ponzi schemes do not yet exist. The method used in this research is a normative research method with a normative juridical approach or a statutory approach. The research findings show that to ensnare the perpetrators of illegal investment crimes and pyramid schemes there are already laws and regulations governing this matter, while the perpetrators of crimes with ponzi schemes still use the rules prohibiting illegal investment in general and regulations regarding the prohibition of pyramid schemes, while pyramid schemes and ponzi schemes are different things, legal protection for victims, especially regarding the return of illegal investment money using pyramid schemes and ponzi schemes, is still difficult to do at this time.